Health inequalities, physician citizens and professional medical associations: an Australian case study - Naccarella Lucio; Harris Mark; Harris Elizabeth; Furler John; Young Doris; Snowdon Teri (BMC Medicine, 2007)
Abstract Background As socioeconomic health inequalities persist and widen, the health effects of adversity are a constant presence in the daily work of physicians. Gruen and colleagues suggest that, in responding to important population health issues such as this, defining those areas of professional obligation in contrast to professional aspiration should be on the basis of evidence and feasibility. Drawing this line between obligation and aspiration is a part of the work of professional medical colleges and associations, and in doing so they must respond to members as well as a range of other interest groups. Our aim was to explore the usefulness of Gruen's model of physician responsibility in defining how professional medical colleges and associations should lead the profession in responding to socioeconomic health inequalities. Methods We report a case study of how the Royal Australian College of General Practitioners is responding to the issue of health inequalities through its work. We undertook a consultation (80 interviews with stakeholders internal and external to the College and two focus groups with general practitioners) and program and policy review of core programs of College interest and responsibility: general practitioner training and setting of practice standards, as well as its work in public advocacy. Results Some strategies within each of these College program areas were seen as legitimate professional obligations in responding to socioeconomic health inequality. However, other strategies, while potentially professional obligations within Gruen's model, were nevertheless contested. The key difference between these lay in different moral orientations. Actions where agreement existed were based on an ethos of care and compassion. Actions that were contested were based on an ethos of justice and human rights. Conclusion Colleges and professional medical associations have a role in explicitly leading a debate about values, engaging both external stakeholder and practicing member constituencies. This is an important and necessary step in defining an agreed role for the profession in addressing health inequalities.